Nanoparticle delivery system, highly active antiretroviral therapy, and testicular morphology: The role of stereology - Edwin Coleridge S. Naidu; Samuel Oluwaseun Olojede; Sodiq Kolawole Lawal; Carmen Olivia Rennie; Onyemaechi Okpara Azu (Wiley, 2021)
Abstract The conjugation of nanoparticles (NPs) with antiretroviral drugs is a drug delivery approach with great potential for managing HIV infections. Despite their promise, recent studies have highlighted the toxic effects of nanoparticles on testicular tissue and their impact on sperm morphology. This review explores the role of stereological techniques in assessing the testicular morphology in highly active antiretroviral therapy (HAART) when a nanoparticle drug delivery system is used. Also, NPs penetration and pharmacokinetics concerning the testicular tissue and blood-testis barrier form the vital part of this review. More so, various classes of NPs employed in biomedical and clinical research to deliver antiretroviral drugs were thoroughly discussed. In addition, considerations for minimizing nanoparticle‐drugs toxicity, ensuring enhanced permeability of nanoparticles, maximizing drug efficacy, ensuring adequate bioavailability, and formulation of HAART‐NPs fabrication are well discussed.